Low-power fully monolithic MICS band receiver for 402-405 MHz implantable devices. Issue 1 (2nd January 2020) - Shawkey, Heba; Saleh, Sherif
ABSTRACT: A 402–405MHz fully monolithic Radio Frequency (RF) low-Intermediate Frequency (IF) receiver is presented. The proposed low-power RF receiver consists of a differential Common gate-Common Source Low-Noise Amplifier (CG-CS LNA) with a positive–negative feedback technique, passive mixer, fully integrated Voltage Controlled Oscillator (VCO), and an IF Variable Gain Amplifier (VGA). To achieve a wide tuning range while keeping a low gain (Kvco), the VCO has 16 bands selectable by a 4-bit digital control. The complete receiver prototype is implemented in a 0.13 μm CMOS process and occupies 0.625 mm 2 active chip area. The receiver consumes only 3.76 mW of power from a 1.2 V power supply and has a gain of 45 dB and a noise figure of 13.6 dB (integrated from 20 Hz to 0.5 GHz). The design achieves an in-band IIP3 of 2 dBm, IIP2 better than 44 dBm. It presents a 3-dB IF bandwidth of 3 MHz with −80 dBm sensitivity.